Genome-wide association analysis of key genes for feed efficiency in Qingyuan Partridge chickens - Fei Ye; Hongwei Jie; Jiankang Gan; Kunyu Liu; Zhengfen Zhang; Hai Xiang; Wei Liu; Qiong Yin; Siyu Chen; Hui Yu; Hua Li (Poultry Science)
Qingyuan Partridge chickens represent a notable breed of high-quality, slow-growing chickens. The cost of feed constitutes 65-70 % of the total breeding expense for Qingyuan Partridge chickens. Enhancing feed utilization efficiency and reducing feed consumption are crucial for the advancement of Qingyuan Partridge chickens and the broader poultry industry. To investigate the key candidate genes associated with feed efficiency in Qingyuan Partridge chickens for genome selection, the genome-wide association study (GWAS) was performed in this study. Genetic parameters estimation results indiated that the heritability of 12-17 feed conversion ratio was 0.19, with the highest genetic correlation observed with 17 body weight (-0.96). Additionally, the heritability of 12-17 residual feed intake was 0.09, with the highest genetic correlation with 12-14 average daily feed intake (0.93). GWAS results revealed 28 significant SNPs associated with body weight, feed intake, metabolic weight, weight gain, feed conversion ratio, and residual feed intake. The multiple genes are significantly enriched in the aromatic compound biosynthetic process, heterocycle biosynthetic process, and nucleobase-containing compound biosynthetic process. Quantitative reverse transcription polymerase chain reaction (qRT-PCR) analysis showed that the expression levels of four genes—exocyst complex component 4(EXOC4), fibrosin like 1(FBRSL1), methionine adenosyltransferase 2 non-catalytic beta subunit (MAT2B), and cytidine/uridine monophosphate kinase 1(CMPK1)—related to significant SNPs exhibited significant differences in the liver tissues of high residual feed intake group compared with low residual feed intake group. These findings contribute to a better understanding of the molecular mechanisms underlying chicken feed efficiency traits, enabling further genetic improvement of Qingyuan Partridge chickens, and improving industrial efficiency.